Plant virology in Africa [2] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Plant virology in AfricaDr Mawuena Y. Dieudonne Gumedzoe of the University of Benin also writes in support of The future of plant virology in Africa. 'Virologists have to make practical proposals to policy makers. It is a good idea that an African...